Porous filter ceramic prepared from FCC (fluid catalytic cracking) waste catalyst and waste alumina grinding ball powder as well as preparation method and application of porous filter ceramic

By preparing porous filter ceramics, and using FCC waste catalyst and waste alumina grinding ball powder to sinter with materials such as fibers at high temperature, the balance between air permeability and mechanical properties of porous microporous filter ceramics was solved, and efficient preparation suitable for filter materials was achieved.

CN119118699APending Publication Date: 2024-12-13ZIBO VOCATIONAL INST
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411072424.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing technologies have failed to effectively utilize FCC waste catalysts and waste alumina grinding balls to prepare porous microporous filter ceramics, making it difficult to ensure both air permeability and good mechanical properties.

Method used

Using FCC waste catalyst and waste alumina grinding ball powder as the main raw materials, the porous filter ceramic is prepared by activating and mixing it with fiber, binder, dispersant and foaming agent, and sintering at high temperature to form a porous microporous network skeleton.

Benefits of technology

The prepared porous filter ceramics have excellent mechanical properties while ensuring good air permeability, making them suitable for large-scale production and applicable to filter materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118699A_ABST
    Figure CN119118699A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic non-metallic materials, and particularly relates to porous filter ceramic prepared from FCC waste catalyst and waste aluminum oxide grinding ball powder and a preparation method and application of the porous filter ceramic. The material is prepared from the following raw materials: an activated FCC waste catalyst, activated waste Al2O3 grinding ball powder, fibers, a binder, a dispersant, a foaming agent and starch. According to the method, the FCC waste catalyst and the waste aluminum oxide grinding ball powder are activated, and due to the fact that the FCC waste catalyst and the waste aluminum oxide grinding ball powder are smooth in particle surface and low in reaction activity, after the FCC waste catalyst and the waste aluminum oxide grinding ball powder are soaked in the homologous precursor solution and calcined at the low temperature, the particles are exposed, the grain boundary is rough, the reaction activity is improved, and the material performance is improved. The porous filtering ceramic prepared by the invention has good mechanical properties under the condition of ensuring good air permeability, and can play a good filtering role.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic non-metallic materials, and in particular relates to a porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder, and a preparation method and application thereof. Background Art

[0002] Fluid Catalytic Cracking (FCC) is an important technology in the catalytic cracking process of petroleum. The process is mainly carried out through a fluidized bed reactor, and heavy oil is converted into light oil and high value-added chemicals through the action of catalysts. During the catalytic cracking process, high temperature and heavy metal poisoning cause the catalyst activity to decrease and cannot meet the reaction requirements. These deactivated catalysts need to be discharged regularly, resulting in a large amount of FCC waste catalysts.

[0003] According to statistics, the world produces about 2,300 tons of FCC catalysts every day, about 840,000 tons per year. At present, my country's catalytic cracking capacity ranks second in the world, and the number of catalysts consumed each year is more than 200,000 tons. With the heavy and inferior quality of oil resources, the replacement cycle of catalytic cracking catalysts has been significantly shortened, and the heavy metal pollution problem of waste catalysts has become increasingly prominent. In addition, FCC waste catalysts contain nickel elements, and after calcination at 700°C, the nickel elements exist in the form of nickel oxide with a mass fraction of more than 0.1%. Since nickel oxide is a Class I carcinogenic substance, the "National List of Hazardous Wastes" issued on August 1, 2016 classifies FCC waste catalysts as HW50 waste catalyst hazardous waste. Under such circumstances, the treatment of FCC waste catalysts is urgent.

[0004] The main component of FCC spent catalyst is alumina (Al 2 O 3 ) and silicon dioxide (SiO 2 ), and other small amounts of rare earth elements, heavy metals, etc. Considering that the main component of FCC waste catalyst is close to Al 2 O 3 -SiO 2 The composition of ceramics can be used to prepare high-temperature resistant porous microporous filtration ceramic materials with FCC waste catalyst as raw material. In addition, alumina grinding balls are a kind of abrasive media with excellent wear resistance. Due to its excellent hardness and wear resistance, it is an ideal grinding medium for modern mining, cement, ceramics and chemical industries. However, during the long grinding process, the balls collide with each other, causing the grinding balls to break, or the ball diameter size to decrease, which cannot meet the working size requirements and become solid waste. The Al content of alumina grinding balls is above 90%. Recycling them can not only increase the utilization rate of Al, but also reduce environmental pollution.

[0005] Patent CN110002855A discloses a high temperature resistant foam ceramic prepared from FCC waste catalyst. The high temperature foam ceramic prepared by this process has the characteristics of moderate density, low thermal conductivity, and can be used for a long time at high temperature. At the same time, the high temperature resistant foam ceramic provided by the present invention uses FCC waste catalyst as the preparation raw material, realizing the efficient recycling and reuse of FCC waste catalyst.

[0006] Patent CN116003114A discloses a method for preparing a foamed ceramic material from FCC waste catalyst. The preparation process uses FCC waste catalyst, albite, aeolian sand, talc, silicon carbide, and sodium tripolyphosphate as raw materials, and is made by high-temperature foaming and firing. The foamed ceramic material has a porous structure, which solves the problems of serious pollution of FCC waste catalyst and poor toughness and low strength of existing foamed ceramic products.

[0007] Patent CN117105652A discloses a method for preparing mullite material by low temperature sintering of FCC waste catalyst and fly ash and the prepared mullite material. FCC waste catalyst is the main material, fly ash waste is the auxiliary material, and bauxite tailings, kyanite tailings, Al 2 O 3 Powder, sintering aid, mullite material obtained through batching, grinding, molding, and low-temperature sintering process. Mullite material is prepared by low-temperature sintering of FCC waste catalyst and fly ash. The amount of FCC waste catalyst and fly ash added is high, the preparation process is simple, and the cost is low; the addition of sintering aid can reduce the sintering temperature, greatly shorten the sintering time, reduce energy consumption, and improve the mechanical strength, high temperature resistance and density of the product.

[0008] Patent CN115650251A discloses a MOR zeolite molecular sieve monolith and its preparation method and application. Alkali source, water, FCC waste catalyst and silicon source are mixed to obtain a mixed solution; the mixed solution is hydrothermally zeolized to obtain a MOR zeolite molecular sieve monolith; the temperature of the hydrothermal zeolization is 140~200℃. The present invention uses FCC waste catalyst as raw material instead of pure chemical reagents, which solves the problem of handling and storing FCC waste catalyst and greatly reduces the production cost of zeolite molecular sieve.

[0009] Through the review of literature and patents, no porous microporous filtration ceramics and their preparation methods have been found using FCC waste catalysts and waste alumina grinding balls. Porous microporous filtration ceramics have important applications in industrial metallurgy, waste gas treatment and aerospace. There are few reports on the research and preparation methods of porous filtration ceramic materials using FCC waste catalysts and high-temperature resistant fibers. Therefore, the research and preparation of high-temperature resistant porous microporous filtration ceramics is of great significance. Summary of the invention

[0010] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder, wherein the obtained porous filter ceramic has good mechanical properties while ensuring good air permeability.

[0011] The invention also provides a preparation method thereof, which is simple and feasible and suitable for large-scale production.

[0012] The invention also provides an application of the invention, which is used as a filter material and can play a good filtering role.

[0013] The porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder of the present invention is prepared from the following raw materials in parts by mass: 55-100 parts of activated FCC spent catalyst; Activated waste Al 2 O 3 Grinding ball powder 0-45 parts; Fiber 2-20 parts; 2-10 parts of adhesive; Dispersant 0.5-1.5 parts; 0.5-5 parts of foaming agent; 15-40 parts of starch; The fibers are quartz fibers, high-silicon aluminum fibers, mullite fibers, alumina fibers and / or zirconia fibers.

[0014] The activation process of the FCC waste catalyst comprises the following steps: placing the FCC waste catalyst in silica sol and aluminum sol for immersion and stirring, and then filtering, drying, burning, cooling, and grinding to obtain the catalyst; The waste Al 2 O 3 The activation process of grinding balls includes the following steps: 2 O 3 The grinding balls are crushed and milled into powders with a median size of 60μm, 80μm, 100μm or 200μm. 2 O 3 The powder is immersed in green sol and stirred, and then filtered, dried, burned, cooled and ground to obtain the product; The SiO in the silica sol 2 The content of Al in the aluminum sol is 20wt%-30wt%; 2 O 3 The mass fraction is 20wt%-25wt%.

[0015] The binder is aluminum dihydrogen phosphate; the dispersant is polyacrylamide; the foaming agent is sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and / or triethanolamine lauryl sulfate; and the starch is wheat starch, corn starch and / or potato starch.

[0016] Further, the particle size of the FCC waste catalyst is 60-200 μm; The waste Al 2 O 3 The particle size of the grinding ball powder is 60-200μm; The waste Al 2 O 3 Al grinding ball powder 2 O 3 Mass content ≥90%; The diameter of the fiber is 2-10 μm; The aspect ratio of the fiber is 2-10; The SiO 2 Mass content ≥90%; The Al 2 O 3 Mass content ≥44%; The Al 2 O 3 Mass content ≥72%; The Al2O3 fiber 2 O 3 Mass content ≥95%; The ZrO 2 Mass content ≥96%.

[0017] Furthermore, the particle size of the FCC waste catalyst is 60 μm, 80 μm, 100 μm or 200 μm; 2 O 3 The particle size of the grinding ball powder is 60 μm, 80 μm, 100 μm or 200 μm.

[0018] Further preferably, the particle size of the FCC waste catalyst is 60 μm or 80 μm; 2 O 3 The particle size of the grinding ball powder is 60 μm or 80 μm.

[0019] Preferably, the porous filter ceramic made from FCC waste catalyst is prepared from the following raw materials in parts by weight: 55-100 parts of activated FCC spent catalyst; Activated waste Al 2 O 3Grinding ball powder 15-45 parts; Fiber 2-20 parts; 2-10 parts of adhesive; Dispersant 0.5-1.5 parts; 0.5-5 parts of foaming agent; 15-40 parts of starch.

[0020] The porous filter ceramic is preferably prepared from the following raw materials in parts by weight: ① 55g of activated FCC waste catalyst and activated waste Al 2 O 3 Grinding ball powder 45g, zirconium oxide fiber 10g, aluminum dihydrogen phosphate 6.6g, polyacrylamide 1g, sodium dodecyl sulfate 2g, wheat starch 33g; ② 85g of activated FCC waste catalyst and activated waste Al 2 O 3 Grinding ball powder 15g, alumina fiber 10g, aluminum dihydrogen phosphate 6.6g, polyacrylamide 1g, sodium dodecylbenzene sulfonate 3g, wheat starch 33g; ③ 65g of activated FCC waste catalyst, activated waste Al 2 O 3 Grinding ball powder 45g, mullite fiber 10g, aluminum dihydrogen phosphate 4.6g, polyacrylamide 0.8g, triethanolamine lauryl sulfate 3g, corn starch 20g; ④ 75g of activated FCC waste catalyst and activated waste Al 2 O 3 Grinding ball powder 25g, high silicon aluminum fiber 2g, aluminum dihydrogen phosphate 2g, polyacrylamide 0.5g, triethanolamine lauryl sulfate 1g, potato starch 30g; ⑤ 85g of activated FCC waste catalyst, 15g of high-silica aluminum fiber, 4g of aluminum dihydrogen phosphate, 0.65g of polyacrylamide, 1g of triethanolamine lauryl sulfate, and 20g of potato starch.

[0021] The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder of the present invention comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst is placed in silica sol and aluminum sol, immersed and stirred, filtered, dried at 30-80℃ for 12-36h, then heated to 150-350℃ and burned for 2-6h, cooled, and ground to obtain; (2) Waste Al 2 O 3 Activation of grinding ball powder: Waste Al2 O 3 The grinding ball powder is immersed in aluminum sol and stirred, filtered, dried at 30-80℃ for 12-36h, then heated to 150-350℃ for burning, cooled, and ground to obtain; (3) The activated FCC waste catalyst and the activated waste Al 2 O 3 The grinding ball powder, fiber, binder, dispersant, foaming agent, starch and 100 parts by weight of water are uniformly mixed to obtain a mixed slurry; (4) The obtained mixed slurry is stirred and foamed for 2 to 5 minutes, poured into a porous mold, and allowed to stand to obtain a wet blank; (5) Wet billet drying: drying at 30-50°C for 36-72 hours, then heating to 90-100°C and drying for 4-10 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry billet is fired in a kiln at 1150-1250℃ for 1-3 hours, and then at 1400-1650℃ for 4-12 hours.

[0022] The porous filter ceramics made from FCC waste catalyst of the present invention are used as filter materials.

[0023] The porous filter ceramic has an apparent porosity of 24%-70%; the pore surface area of ​​the porous filter ceramic is 0.05-3 g / m 2 .

[0024] Compared with the prior art, the present invention has the following beneficial effects: 1) The present invention converts FCC waste catalyst and waste Al 2 O 3 Grinding ball powder for activation, due to FCC waste catalyst and waste Al 2 O 3 The grinding ball powder particles have a smooth surface and low reactivity. The present invention makes the exposed grain boundaries of the particles rough by impregnating them with a homologous precursor solution and calcining them at a low temperature, thereby improving the reactivity and the material performance.

[0025] 2) The present invention uses FCC waste catalyst and waste Al 2 O 3 Grinding ball powder is used as the main raw material, and ceramic fibers such as zirconia fiber are used as reinforcements, supplemented with binders, dispersants and stabilizers to prepare the molding slurry, which is sintered at high temperature to form a porous microporous network skeleton. It has good mechanical properties while ensuring good air permeability and can play a good filtering role.

[0026] 3) The preparation method described in the present invention is scientific and reasonable, easy to implement in production, and has the advantages of safety, environmental protection, speed, low investment cost, etc., and is suitable for industrial promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the appearance of the porous filter ceramic obtained in Example 1. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto.

[0029] Definitions of terms used in the present invention: Unless otherwise stated, the initial definitions provided for groups or terms in this document apply to the groups or terms throughout the specification; for terms that are not specifically defined in this document, the meaning that a person skilled in the art can give them should be given based on the disclosure and context.

[0030] The raw materials and equipment used in the specific embodiments of the present invention are all known products and are obtained by purchasing commercially available products.

[0031] FCC spent catalyst (Fluid Catalytic Cracking, FCC for short): particle size is 60-200μm, and the main components (mass fraction) are as follows:

[0032] Waste Al 2 O 3 Grinding ball powder: particle size 60-200μm, Al 2 O 3 Mass content ≥90%; Quartz fiber: diameter 3-10μm, aspect ratio 2-10, SiO 2 Mass content ≥90%; High silicon aluminum fiber: diameter is 3-10μm, aspect ratio is 2-10, Al 2 O 3 Mass content ≥44%; Mullite fiber: diameter is 2-10μm, aspect ratio is 2-10, Al 2 O 3 Mass content ≥72%; Alumina fiber: diameter is 2-10μm, aspect ratio is 2-10, Al 2 O 3 Mass content ≥95%; Zirconia fiber: diameter is 2-10μm, aspect ratio is 2-10, ZrO 2 Mass content ≥96%; Silica sol: chemically pure, SiO 2 Mass content: 20-30%; Aluminum sol: chemically pure, Al2 O 3 Mass content: 20-25%; Binder: aluminum dihydrogen phosphate, chemically pure; Dispersant: polyacrylamide (PAM), analytical grade; Foaming agent: sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, triethanolamine lauryl sulfate, analytical grade; Stabilizers: wheat starch, corn starch and potato starch, food grade.

[0033] Example 1 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 60 μm was immersed and stirred in 20 wt% silica sol and 20 wt% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for 5 h, cooled, and ground to obtain an activated FCC waste catalyst; (2) Waste Al 2 O 3 Activation of grinding ball powder: The scrap Al with an average particle size of 60 μm 2 O 3 The ball powder was ground and placed in 20wt% aluminum sol for 10 min, filtered, dried in a 50℃ oven for 24 h, and then placed in a muffle furnace and heated to 300℃ for 5 h, cooled, and ground to obtain the activated waste Al 2 O 3 grinding ball powder; (3) Take 55g of activated FCC waste catalyst and activated waste Al 2 O 3 45 g of grinding ball powder, 10 g of zirconium oxide fiber, 6.6 g of aluminum dihydrogen phosphate, 1 g of polyacrylamide, 2 g of sodium dodecyl sulfate, 33 g of wheat starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (4) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (5) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200℃ for 1 hour and then at 1540℃ for 4 hours to obtain porous filter ceramic TC1, which has the following appearance: Figure 1 shown.

[0034] Example 2 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 200 μm was immersed and stirred in 30 wt% silica sol and 25 wt% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for 5 h, cooled, and ground to obtain the activated FCC waste catalyst; (2) Waste Al 2 O 3 Activation of grinding ball powder: The scrap Al with an average particle size of 200 μm 2 O 3 The ball powder was ground and placed in 25wt% aluminum sol for 10 min, filtered, dried in a 50℃ oven for 24 h, and then placed in a muffle furnace and heated to 300℃ for 5 h, cooled, and ground to obtain the activated waste Al 2 O 3 grinding ball powder; (3) Take 85g of activated FCC waste catalyst and activated waste Al 2 O 3 15 g of grinding ball powder, 10 g of alumina fiber, 6.6 g of aluminum dihydrogen phosphate, 1 g of polyacrylamide, 3 g of sodium dodecylbenzene sulfonate, 33 g of wheat starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (4) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (5) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1500°C for 4 hours to obtain porous filter ceramic TC2.

[0035] Example 3 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 100 μm was immersed and stirred in 30 wt% silica sol and 25 wt% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for 5 h, cooled, and ground to obtain an activated FCC waste catalyst; (2) Waste Al 2 O 3 Activation of grinding ball powder: The scrap Al with an average particle size of 200 μm 2 O 3 The ball powder was ground and placed in 25wt% aluminum sol for 10 min, filtered, dried in a 50℃ oven for 24 h, and then placed in a muffle furnace and heated to 300℃ for 5 h, cooled, and ground to obtain the activated waste Al 2 O 3 grinding ball powder; (3) Take 65g of activated FCC waste catalyst and activated waste Al 2 O 3 45 g of grinding ball powder, 10 g of mullite fiber, 4.6 g of aluminum dihydrogen phosphate, 0.8 g of polyacrylamide, 3 g of triethanolamine lauryl sulfate, 20 g of corn starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (4) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (5) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1480°C for 4 hours to obtain porous filter ceramic TC3.

[0036] Example 4 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 200 μm was immersed and stirred in 30 wt% silica sol and 25 wt% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for 5 h, cooled, and ground to obtain an activated FCC waste catalyst; (2) Waste Al 2 O 3 Activation of grinding ball powder: The scrap Al with an average particle size of 100 μm 2 O 3 The ball powder was ground and placed in 25wt% aluminum sol for 10 min, filtered, dried in a 50℃ oven for 24 h, and then placed in a muffle furnace and heated to 300℃ for 5 h, cooled, and ground to obtain the activated waste Al 2 O 3grinding ball powder; (3) Take 75g of activated FCC waste catalyst and activated waste Al 2 O 3 25 g of grinding ball powder, 2 g of high-silica aluminum fiber, 2 g of aluminum dihydrogen phosphate, 0.5 g of polyacrylamide, 1 g of triethanolamine lauryl sulfate, 30 g of potato starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (4) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (5) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1400°C for 4 hours to obtain porous filter ceramic TC4.

[0037] Example 5 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 80 μm was immersed and stirred in 30 wt% silica sol and 25 wt% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for calcination for 5 h, cooled, and ground to obtain the activated FCC waste catalyst; (2) 85 g of activated FCC waste catalyst, 15 g of high-silica aluminum fiber, 4 g of aluminum dihydrogen phosphate, 0.65 g of polyacrylamide, 1 g of triethanolamine lauryl sulfate, 20 g of potato starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (3) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (4) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain dry billet; (5) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1400°C for 4 hours to obtain porous filter ceramic TC5.

[0038] Comparative Example 1 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Waste Al 2 O 3 Activation of grinding ball powder: The scrap Al with an average particle size of 60 μm 2 O 3 The ball powder was ground and placed in 25wt% aluminum sol for 10 min, filtered, dried in a 50℃ oven for 24 h, and then placed in a muffle furnace and heated to 300℃ for 5 h, cooled, and ground to obtain the activated waste Al 2 O 3 grinding ball powder; (2) Take 55g of FCC waste catalyst and activated waste Al 2 O 3 45 g of grinding ball powder, 10 g of zirconium oxide fiber, 6.6 g of aluminum dihydrogen phosphate, 1 g of polyacrylamide, 2 g of sodium dodecyl sulfate, 33 g of wheat starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (3) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (4) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain dry billet; (5) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1540°C for 4 hours to obtain the porous filter ceramic DTC1.

[0039] Comparative Example 2 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 60 μm was immersed and stirred in 20 wt% silica sol and 20 wt% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for 5 h, cooled, and ground to obtain an activated FCC waste catalyst; (2) Take 55g of activated FCC waste catalyst and waste Al 2 O 3 45 g of grinding ball powder, 10 g of zirconium oxide fiber, 6.6 g of aluminum dihydrogen phosphate, 1 g of polyacrylamide, 2 g of sodium dodecyl sulfate, 33 g of wheat starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (3) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (4) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain dry billet; (5) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1540°C for 4 hours to obtain the porous filter ceramic DTC2.

[0040] Comparative Example 3 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Take 55g of FCC waste catalyst and waste Al 2 O 3 45 g of grinding ball powder, 10 g of zirconium oxide fiber, 6.6 g of aluminum dihydrogen phosphate, 1 g of polyacrylamide, 2 g of sodium dodecyl sulfate, 33 g of wheat starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (2) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (3) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain dry billet; (4) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1540°C for 4 hours to obtain the porous filter ceramic DTC3.

[0041] Comparative Example 4 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 60 μm was immersed and stirred in 20 wt% silica sol and 20 wt% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for 5 h, cooled, and ground to obtain an activated FCC waste catalyst; (2) Waste Al 2 O 3 Activation of grinding ball powder: The scrap Al with an average particle size of 60 μm 2 O 3 The ball powder was ground and placed in 20wt% aluminum sol for 10 min, filtered, dried in a 50℃ oven for 24 h, and then placed in a muffle furnace and heated to 300℃ for 5 h, cooled, and ground to obtain the activated waste Al 2 O 3 grinding ball powder; (3) Take 55g of activated FCC waste catalyst and activated waste Al 2 O 345 g of grinding ball powder, 10 g of zirconium oxide fiber, 6.6 g of aluminum dihydrogen phosphate, 1 g of polyacrylamide, 2 g of sodium dodecyl sulfate, 33 g of wheat starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (4) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (5) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1300°C for 4 hours to obtain the porous filter ceramic DTC4.

[0042] Comparative Example 5 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 100 μm was immersed and stirred in 30 wt% silica sol and 25 wt% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for 5 h, cooled, and ground to obtain an activated FCC waste catalyst; (2) Waste Al 2 O 3 Activation of grinding ball powder: The scrap Al with an average particle size of 200 μm 2 O 3 The ball powder was ground and placed in 25wt% aluminum sol for 10 min, filtered, dried in a 50℃ oven for 24 h, and then placed in a muffle furnace and heated to 300℃ for 5 h, cooled, and ground to obtain the activated waste Al 2 O 3 grinding ball powder; (3) Take 65g of activated FCC waste catalyst and activated waste Al 2 O 3 45 g of grinding ball powder, 10 g of mullite fiber, 4.6 g of aluminum dihydrogen phosphate, 0.8 g of polyacrylamide, 3 g of triethanolamine lauryl sulfate, 20 g of corn starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (4) The obtained mixed slurry is foamed under stirring in a stirrer (time 10 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (5) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1480°C for 4 hours to obtain the porous filter ceramic DTC5.

[0043] Comparative Example 6 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 200 μm was immersed and stirred in 30 wt% silica sol and 25% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for 5 h, cooled, and ground to obtain an activated FCC waste catalyst; (2) Waste Al 2 O 3 Activation of grinding ball powder: The scrap Al with an average particle size of 100 μm 2 O 3 The ball powder was ground and placed in 25% aluminum sol for 10 min, filtered, dried in a 50 °C oven for 24 h, and then placed in a muffle furnace and heated to 300 °C for 5 h, cooled, and ground to obtain the activated waste Al 2 O 3 grinding ball powder; (3) Take 75g of activated FCC waste catalyst and activated waste Al 2 O 3 25 g of grinding ball powder, 2 g of aluminum dihydrogen phosphate, 0.5 g of polyacrylamide, 1 g of triethanolamine lauryl sulfate, 30 g of potato starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (4) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (5) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1400°C for 4 hours to obtain the porous filter ceramic DTC6.

[0044] Comparative Example 7 The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder comprises the following steps: (1) Activation of FCC spent catalyst: The FCC waste catalyst with an average particle size of 60 μm was immersed and stirred in 20 wt% silica sol and 20 wt% aluminum sol for 10 min, filtered, placed in a 50°C oven for drying for 24 h, then placed in a muffle furnace and heated to 300°C for 5 h, cooled, and ground to obtain an activated FCC waste catalyst; (2) Waste Al 2 O 3 Activation of grinding ball powder: The scrap Al with an average particle size of 60 μm 2 O 3 The ball powder was ground and placed in 20wt% aluminum sol for 10 min, filtered, dried in a 50℃ oven for 24 h, and then placed in a muffle furnace and heated to 300℃ for 5 h, cooled, and ground to obtain the activated waste Al 2 O 3 grinding ball powder; (3) Take 55g of activated FCC waste catalyst and activated waste Al 2 O 3 45 g of grinding ball powder, 10 g of alumina fiber, 1 g of polyacrylamide, 2 g of sodium dodecyl sulfate, 33 g of wheat starch and 100 g of deionized water were mixed uniformly to obtain a mixed slurry; (4) The obtained mixed slurry is foamed under stirring in a stirrer (time 5 min), poured into a porous mold, and allowed to stand (20 min) to obtain a wet blank; (5) Drying of wet billet: drying at 40°C for 48 hours, then drying at 100°C for 4 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry blank is fired in a kiln at 1200°C for 1 hour and then at 1540°C for 4 hours to obtain porous filter ceramic TC7.

[0045] Performance Test: 1. Apparent porosity test of porous ceramics The apparent porosity test of porous ceramics is based on GB / T 2997-2015 (test method for bulk density, apparent porosity and true porosity of dense shaped refractory products). Dry the ultrasonically cleaned sample in a drying oven at 110 ± 5℃ for at least 2 h, place it in a desiccator and wait for it to cool naturally to room temperature before weighing the sample mass m. 1 Place the sample in a beaker and immerse it in distilled water. Boil it for 1 hour and then cool it naturally to room temperature. Use tweezers to carefully remove the sample and wipe off the excess water on the surface, but be careful not to suck out the water in the sample hole. Immediately weigh the mass of the immersed sample in the air m 3 Place the sample in a lightweight mesh and immerse it in water to a certain depth without touching the wall or bottom of the water container. Weigh the mass m of the sample immersed in water.2 .

[0046] The apparent porosity P and bulk density D of the sample were calculated by equations (1) and (2), respectively, where ρ is the density of distilled water, 1.00 g / cm 3 .

[0047] 2. Pore size and surface area test This experiment uses a high-performance fully automatic mercury intrusion instrument, Autopore IV 9500, with a pressure range of 0-414 MPa. The sample is fully dried and cooled in a constant temperature drying oven before the experiment. The surface tension of mercury is 0.485 N / m, the contact angle between mercury and the sample is 130°, and the density of mercury is 13.53 g / mL.

[0048] 3. Compressive strength test, refer to JC / T 945-2005. Use the universal mechanical testing machine model INSTRON 5982, remove the sticky residue and burrs on the surface of the sample, soak it in room temperature water for 24 hours, take it out and wipe off the surface attached water with a wrung wet towel, place it in the center of the lower pressure plate of the testing machine, start the testing machine, adjust the loading speed to 0.4 ~ 0.6MPa / s, and load evenly and continuously until the sample is destroyed, and record the failure load when the sample is destroyed.

[0049] The measurement results of the porous filter ceramics obtained in the above examples are shown in Table 1.

[0050] Table 1 Measurement results of porous filter ceramics in Example

[0051] The measurement results of the porous filter ceramics obtained in the above comparative examples are shown in Table 2.

[0052] Table 2 Test results of comparative porous filter ceramics

[0053] The results show that the present invention uses FCC waste catalyst and waste Al 2 O 3 Grinding balls are used as the main raw material, and ceramic fibers such as zirconia fibers with low thermal conductivity, corrosion resistance, high temperature resistance and good stability are used as reinforcements. Binders, dispersants and stabilizers are used to prepare the molding slurry, which is sintered at high temperature to form a porous microporous network skeleton. It has good mechanical properties while ensuring good air permeability and can play a good filtering role.

[0054] In addition, the preparation method of the porous filter ceramic of the present invention is scientific and reasonable, easy to implement in production, and has the advantages of safety, environmental protection, speed, and low investment cost, and is suitable for industrial promotion and use.

Claims

1. A porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder, It is characterized in that It is prepared from the following raw materials in parts by weight: 55-100 parts of activated FCC spent catalyst; Activated waste Al 2 O 3 Grinding ball powder 0-45 parts; Fiber 2-20 parts; 2-10 parts of adhesive; Dispersant 0.5-1.5 parts; 0.5-5 parts of foaming agent; 15-40 parts of starch; The fibers are quartz fibers, high-silicon aluminum fibers, mullite fibers, alumina fibers and / or zirconia fibers.

2. The porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder according to claim 1, It is characterized in that The activation process of the FCC waste catalyst comprises the following steps: placing the FCC waste catalyst in silica sol and aluminum sol for immersion and stirring, and then filtering, drying, burning, cooling, and grinding to obtain the catalyst; The waste Al 2 O 3 The activation process of grinding ball powder includes the following steps: 2 O 3 The grinding ball powder is immersed and stirred in aluminum sol, and then filtered, dried, burned, cooled and ground to obtain the powder.

3. The porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder according to claim 2, It is characterized in that The SiO in the silica sol 2 The mass fraction of Al in the aluminum sol is 20wt%-30wt%; 2 O 3 The mass fraction is 20wt%-25wt%.

4. The porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder according to claim 1, It is characterized in that The binder is aluminum dihydrogen phosphate; the dispersant is polyacrylamide; the foaming agent is sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and / or triethanolamine lauryl sulfate; and the starch is wheat starch, corn starch and / or potato starch.

5. The porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder according to claim 1, It is characterized in that The particle size of the FCC waste catalyst is 60-200 μm; The waste Al 2 O 3 The particle size of the grinding ball powder is 60-200μm; The waste Al 2 O 3 Al grinding ball powder 2 O 3 Mass content ≥90%; The diameter of the fiber is 2-10 μm; The aspect ratio of the fiber is 2-10; The SiO 2 Mass content ≥90%; The Al of the high-silicon aluminum fiber 2 O 3 Mass content ≥44%; The Al 2 O 3 Mass content ≥72%; The Al2O3 fiber 2 O 3 Mass content ≥95%; The ZrO 2 Mass content ≥96%.

6. The porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder according to claim 5, It is characterized in that The particle size of the FCC waste catalyst is 60 μm, 80 μm, 100 μm or 200 μm; 2 O 3 The particle size of the grinding ball powder is 60 μm, 80 μm, 100 μm or 200 μm.

7. The porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder according to claim 1, It is characterized in that It is prepared from the following raw materials in parts by weight: 55-100 parts of activated FCC spent catalyst; Activated waste Al 2 O 3 Grinding ball powder 15-45 parts; Fiber 2-20 parts; 2-10 parts of adhesive; Dispersant 0.5-1.5 parts; 0.5-5 parts of foaming agent; 15-40 parts of starch.

8. A method for preparing a porous filter ceramic made from FCC waste catalyst and waste alumina grinding ball powder as claimed in any one of claims 1 to 7, It is characterized in that The following steps are involved: (1) Activation of FCC spent catalyst: The FCC waste catalyst is placed in silica sol and aluminum sol, immersed and stirred, filtered, dried, burned, cooled, and ground to obtain; (2) Waste Al 2 O 3 Activation of grinding ball powder: Waste Al 2 O 3 The grinding ball powder is placed in aluminum sol, immersed and stirred, filtered, dried, burned, cooled, and ground to obtain the powder; (3) The activated FCC waste catalyst and waste Al 2 O 3 The grinding ball powder, fiber, binder, dispersant, foaming agent, starch and 100 parts by weight of water are uniformly mixed to obtain a mixed slurry; (4) The obtained mixed slurry is stirred and foamed for 2 to 5 minutes, poured into a porous mold, and allowed to stand to obtain a wet blank; (5) Wet billet drying: drying at 30-50°C for 36-72 hours, then heating to 90-100°C and drying for 4-10 hours to obtain a dry billet; (6) Firing: Under normal pressure, the dry billet is fired in a kiln at 1150-1250℃ for 1-3 hours, and then at 1400-1650℃ for 4-12 hours.

9. The method for preparing the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder according to claim 8, It is characterized in that The drying temperature in step (1) is 30-80°C and the time is 12-36 hours, and the calcination temperature in step (1) is 150-350°C; the drying temperature in step (2) is 30-80°C and the time is 12-36 hours, and the calcination temperature in step (2) is 150-350°C.

10. Use of the porous filter ceramic made of FCC waste catalyst and waste alumina grinding ball powder as claimed in any one of claims 1 to 7, It is characterized in that Used as filter material.

Citation Information

Patent Citations

  • Method for preparing high-density fused quartz ceramic

    CN103342547A

  • Preparation method of Al2O3 and SiO2 porous ceramic membrane support

    CN106045487A

  • Preparing method of porous mullite ceramic

    CN106316444A

  • Micro-pore ceramic filtering purification material

    CN107500731A

  • Low-temperature preparation method of high-strength mullite ceramic

    CN108516814A